2010
DOI: 10.1116/1.3447233
|View full text |Cite
|
Sign up to set email alerts
|

Ferrimagnetic ordering of single crystal Fe1−xGax thin films

Abstract: Molecular beam epitaxy was used to deposit body centered cubic single crystal Fe^Ga, thin films on MgO(OOl) and ZnSe/GaAs(001) substrates well beyond the bulk stability concentration of about 28%. The crystal quality of the substrate surface and each deposited layer was monitored in situ by reflection high energy electron diffraction. The magnetization of the samples as a function of Ga is found to decrease more rapidly than a simple dilution effect, and element-specific x-ray magnetic circular dichroism ascri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…RHEED measurements confirmed that the growth of Fe x Mn 1Àx films remained epitaxial and in the bcc phase down to x ¼ 0.65 but, like Fe growth, 21 is rotated 45 with respect to the MgO(001) surface net. This extends the range of stability for the bcc structure beyond the bulk bcc stability limit of x ¼ 0.88 (Ref.…”
Section: Methodssupporting
confidence: 60%
“…RHEED measurements confirmed that the growth of Fe x Mn 1Àx films remained epitaxial and in the bcc phase down to x ¼ 0.65 but, like Fe growth, 21 is rotated 45 with respect to the MgO(001) surface net. This extends the range of stability for the bcc structure beyond the bulk bcc stability limit of x ¼ 0.88 (Ref.…”
Section: Methodssupporting
confidence: 60%
“…For all growths, the Fe source was always maintained at constant temperature of ~1400 °C (1673 K) assuring a constant rate of Fe deposition while the Mn source was held at various temperatures to achieve different Mn flux rates and therefore different alloy stoichiometries for the films. The films were deposited with the substrate held at 150-160 °C (423-433 K) to ensure good quality, ~20nm thick films [24]. Deposition fluxes were monitored by quadrupole mass spectrometry (QMS).…”
Section: Methodsmentioning
confidence: 99%
“…The 2 nm Fe buffer layer was 5 deposited with the Fe knudsen cell also held at 1320°C which resulted in a deposition rate of about 0.1 nm/minute. An ideal substrate temperature for growth of Fe on MgO was found to be around 160°C [20], and this was used for both the Fe buffer layer and the Co 1-x Mn x growths. The substrate temperature was then reduced to below 100°C for the Al cap layer.…”
Section: Growthmentioning
confidence: 99%